Anticipated stigma and blameless guilt: Mothers' evaluation of life with the sex-linked disorder, hypohidrotic ectodermal dysplasia (XHED). (June 2016) - Clarke, Angus
Abstract: Practical experience of a genetic disorder may influence how parents approach reproduction, if they know their child may be affected by an inherited condition. One important aspect of this practical experience is the stigmatisation which family members may experience or witness. We outline the concept of stigma and how it affects those in families with a condition that impacts upon physical appearance. We then consider the accounts given by females in families affected by the rare sex-linked disorder, X-linked hypohidrotic ectodermal dysplasia (XHED), which principally affects males but can be passed through female carriers to affect their sons. The stigmatisation of affected males is as important in the accounts given by their womenfolk as the physical effects of the condition; this impacts on their talk about transmission of the disorder to the next generation. Perspectives may also change over time. The mothers of affected sons differ from their daughters, who do not yet have children, and from their mothers, who may express more strongly their sense of guilt at having transmitted the condition, despite there being no question of moral culpability. We conclude with suggestions about other contexts where the possibility of stigma may influence reproductive decisions. Highlights: Living with XHED presents physical and social challenges, including stigmatisation. Female carriers observe the stigmatisation that impacts their affected male relatives. Mothers expect that an affected child may be subject to stigmatisation. Such anticipated stigma impacts the way female carriers talk about reproduction. The perspectives of sisters, daughters, mothers and grandmothers on XHED may differ.